Biomass energy in Malaysia: current state and prospects - Mekhilef, Saad; Saidur, Rahman; Safari, Azadeh; Mustaffa, W.E.S.B. (Elsevier, 2011)
Today, energy crisis turn out to be a serious threat towards sustainability for developing countries since their energy demand is growing more rapidly than developed countries. On the other hand, fossil fuels cannot sustain anymore in the near future because of environmental impacts and depletion of the reserves. Malaysia is experiencing drastic growth in population and economy and requires exploring alternative energy sources to support its population and commercial energy demand. Biomass as the fourth largest energy resource in the world is abundant in the country. Malaysia is blessed with tropical and humid climate all year round which is a magnificent opportunity for fully exploiting agriculture and tropical forests potential. Since late 1990, the concept of waste-to-wealth had been promoted and became popular widely. This concept is based on unwanted wastes which are converted into valuable energy while reducing waste generated and increase the economy-efficiency mainly used for cooking, space heating and power generation. Currently, concerted efforts and various biomass energy programs are supporting by the government for development, demonstration and commercialization. This paper intent to present the current state and prospects of biomass utilization and strategies promoted for future developments in Malaysia.